Multiplexing of Multicolor Bioluminescence Resonance Energy Transfer - Breton, Billy (The Biophysical Society, 2010)
Bioluminescence resonance energy transfer (BRET) is increasingly being used to monitor protein-protein interactions and cellular events in cells. However, the ability to monitor multiple events simultaneously is limited by the spectral properties of the existing BRET partners. Taking advantage of newly developed Renilla luciferases and blue-shifted fluorescent proteins (FPs), we explored the possibility of creating novel BRET configurations using a single luciferase substrate and distinct FPs. Three new (to our knowledge) BRET assays leading to distinct color bioluminescence emission were generated and validated. The spectral properties of two of the FPs used (enhanced blue (EB) FP2 and mAmetrine) and the selection of appropriate detection filters permitted the concomitant detection of two independent BRET signals, without cross-interference, in the same cells after addition of a unique substrate for Renilla luciferase-II, coelentrazine-400a. Using individual BRET-based biosensors to monitor the interaction between G-protein-coupled receptors and G-protein subunits or activation of different G-proteins along with the production of a second messenger, we established the proof of principle that two new BRET configurations can be multiplexed to simultaneously monitor two dependent or independent cellular events. The development of this new multiplexed BRET configuration opens the way for concomitant monitoring of various independent biological processes in living cells.